A survey on secured internet of things architecture - U. Harita, Ms; V.DayaSagar, K (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) introduces an inventive and perceptive of a future Internet where users, computing systems, and everyday items owning sensing and actuating abilities cooperate with unique comfort and financial advantages. Many heterogeneous devices get connected and contribute to the IoT and are known as things.Internet of Things (IoT) enables these things to correspond, compute and make decisions on the network. In such a heterogeneous environment, every user of IoT will have a unique purpose to be served in the form of communication and computation. There is a threat that a malicious user can demolish the security and privacy of the network. Hence any application in the environment of IoT is prone to various attacks and threats. At this point, security becomes a high priority in IoT. To ensure security, care must be taken to guarantee confidentiality, authenticity, data integrity and non-repudiation. In this paperaddress various conventional techniques for providing security of IoT devices and present analysis of existing solutions for IoT. Firstly, as security will be a fundamental allowing thing of most IoT applications, mechanisms must also be designed to defend communications enabled by such technologies. Later, we identify some suitable security algorithms.